Properties of RNA Transcriptase in Reovirus Subviral Particles - Levin, Daniel H. (1970)
Subviral particles containing reovirus RNA transcriptase have been isolated from extracts of virus-infected mouse fibroblast cells. The purified particles which lacked the outer protein capsomeres of the mature virion had a buoyant density of 1.43-1.44 g/ml in CsCl and contained all of the double-stranded RNA genome of the intact virus. The particles were free of nuclease activity. RNA synthesis required all four ribonucleoside triphosphates and was dependent on magnesium or manganese; optimal activity required potassium or ammonium ions. In the presence of a ribonucleoside triphosphate regenerating system, reaction rates were linear for 20 hr. RNA yields of 40-fold in excess of input template could be obtained. Completed RNA chains were released from the subviral particles. In the course of RNA synthesis, the double-stranded RNA template was fully conserved. The RNA products formed in vitro displayed profiles in sucrose gradients similar to those found for in vitro reovirus mRNA. The RNA products were single-stranded and did not self-anneal. Over 90 percent of the transcriptase products could be annealed with template double-stranded RNA. The annealed products migrated in acrylamide gels as double-stranded RNA, indicating efficient in vitro transcription.